The Women’s Art Society of Montreal and Its Place in History, 1894-2019 - Keays, Cathy (Autoédition, 2019)
The Women's Art Society of Montreal (WASM) was founded in 1894 by two Montrealers, Mrs. James H. Peck (nee Mary Alice Skelton) and Mary Martha (May) Phillips, with the goal of integrating women into the art world. This organization was the Montreal branch of the Toronto-based Women’s Art Association until 1907, when it broke away from the mother organization to form its own independent Women’s Art Society of Montreal. In 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In 1981, the Society officially adopted a French name: l’Association culturelle des femmes de Montréal, but the organization remained essentially an English support group. In 1998 it began to accept men as members. The author traces the local, national and international events that coincided with each year of the WASM's existence.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montréal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail

L'importance d'un nom : l'adoption des patronymes à Wendake et à Kahnawake, du milieu du XVIIIe siècle au milieu du XXe siècle - Ouellet, Jean-Sébastien (Université du Québec à Montréal, 2019)
Le présent mémoire s'intéresse aux mutations nominales chez les habitant·es des Premières Nations des communautés de Wendake et Kahnawake. En étudiant les registres des mariages qui y sont célébrés ainsi que d'autres sources de différentes natures, il nous a été possible de circonscrire les périodes de transition et d'identifier certains facteurs potentiels ayant pu causer ces transformations. La recherche s'intéresse ainsi à deux périodes de transition distinctes, respectivement à la fin du XVIIIe siècle pour Wendake et durant la première moitié du XXe siècle pour Kahnawake. Durant ces périodes, la vaste majorité des membres des deux communautés de tradition matrilinéaire abandonnent leurs noms uniques iroquoiens pour adopter des noms européanisés et la patrilinéarité. Ces deux transformations se distinguent de nombreuses façons, mais semblent toutes deux se manifester dans un processus de co-intégration culturelle. Il nous semble que l'importance de ces transformations a été historiquement sous-estimée et trop rarement documentée, particulièrement en regard de l'importance sociale de la transmission matrilinéaire sur le fonctionnement social et la valorisation des rôles sexués dans les communautés Mohawk et Huronne-Wendat, toutes deux réputées traditionnellement matrilinéaires. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Kahnawake, Wendake, Mohawk, Huron-Wendat, nom unique, patronyme, nom de famille, genre, race, mutation nominale, transformation nominale, transformation patronymique, nom clanique, matrilinéarité, patrilinéarité, clanisme
https://uqam-bib.on.worldcat.org/oclc/1164147823
Keywords: 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; discipline; histoire; histoire et politique; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppression; thématiques

Les femmes et la vie culturelle à Québec avant la Révolution tranquille - Harvey, Fernand (Cap-aux-Diamants : la revue d'histoire du Québec, 2008)
https://id.erudit.org/iderudit/6856ac
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; discipline; histoire; histoire des femmes*; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1994)
The Women's Arts Society of Montreal was founded in 1894 by Mary Martha Phillips and Mrs. James H. Peck (nee Mary Alice Skelton). The parent body of the Society (The Women's Art Association of Canada) was incorporated in Toronto in 1892. The goal of the Montreal Society was to integrate women into the art world at a time in history when women had few rights and were relegated to other roles. In 1907, the Montreal branch of the Women's Art Association of Canada broke away from the Toronto organization to form their own independent society. During and after the First World War, the Women's Arts Society of Montreal focussed on philanthropic efforts, assisting disabled and convalescing veterans and their families. After 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In the late 1990s the Society began to accept men as members.
Keywords: 1800-1899; 1900-1999; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montreal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail

Maria W. Stewart, America's first Black woman political writer : essays and speeches - Stewart, Maria W. (Indiana University Press., 1987)
En rassemblant et en présentant les œuvres de Stewart, Richardson offre aux lecteurices l'occasion d'étudier les pensées et les paroles de cette influente militante noire, précurseuse de Frederick Douglass et de Sojourner Truth et première noire américaine à donner des conférences pour la défense des droits des femmes, la plaçant dans le contexte du mouvement abolitionniste tourbillonnant.
Keywords: 1800-1899; amériques; antiesclavagisme; approches et analyses; discipline; droits des femmes*; fem1000; femmes* afro-américaines; féminisme noir; histoire; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

Social purity - Anthony, Susan B. (Not For Ourselves Alone | Ken Burns | PBS, 1875)
In the winter of 1875 Miss Anthony prepared her speech on “Social Purity” and gave it first at the Grand Opera House, Chicago, March 14, in the Sunday afternoon Dime lecture course. When she reached the opera house the crowd was so dense she could not get inside and was obliged to go through the engine room and up the back way to the stage. The gentleman who was to introduce her could not make his way through the throng and so this service was gracefully performed by “Long John” Wentworth, who was seated on the stage. At the close of the address, to her surprise, A. Bronson Alcott, Parker Pillsbury and A.J. Grover came up to congratulate her. She had not known they were in the city. Mr.Alcott said: “You have stated here this afternoon, in a fearless manner, truths that I have hardly dare to think, much less to utter.” No other speaker, man or woman, ever had handled this question with such boldness and severity and the lecture produced a great sensation. Even the radical Mrs. Stanton wrote her she would again be asked to speak in Chicago, and Mr. Slayton said that she had ruined her future chances there; nevertheless she was invited by the same committee the following winter.
Keywords: 1800-1899; amériques; approches et analyses; discipline; discours; discours dominant; droits des femmes*; fem1000; histoire; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppression; thématiques; états-unis